2016
DOI: 10.1136/bmjsem-2016-000131
|View full text |Cite
|
Sign up to set email alerts
|

Associations between altered movement patterns during single-leg squat and muscle activity at weight-transfer initiation in individuals with anterior cruciate ligament injury

Abstract: BackgroundLittle is known about factors contributing to the altered movement patterns observed in many individuals with anterior cruciate ligament (ACL) injury. We addressed whether altered muscular activity is such a factor.Methods16 participants with unilateral, non-reconstructed ACL rupture were scored for altered movement patterns according to Test for Substitution Patterns (TSP), which includes the single-leg squat (SLS). Surface electromyography (SEMG), was recorded in the lower extremities at initiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…A decrease in the stiffness of the elastic components could lead to diminished efficiency in the transmission of contractile tension to the bones. Furthermore, human studies have reported changes in the tensile strength of the elastic components following disuse after orthopedic surgery [ 28 ]. Consequently, it is of paramount importance to emphasize targeting the knee extensor mechanism, particularly during the early postoperative period for individuals undergoing OWHTO.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the stiffness of the elastic components could lead to diminished efficiency in the transmission of contractile tension to the bones. Furthermore, human studies have reported changes in the tensile strength of the elastic components following disuse after orthopedic surgery [ 28 ]. Consequently, it is of paramount importance to emphasize targeting the knee extensor mechanism, particularly during the early postoperative period for individuals undergoing OWHTO.…”
Section: Discussionmentioning
confidence: 99%
“…The single-leg squat (SLS) test is a physical examination used by many physical therapists for the assessment of patients with lower limb injury, including those with suspected ACL injuries. The test provides information about a patient’s confidence and stability on one leg, as well as information about knee pain and a patient’s pattern of movement that might be considered undesirable or potentially injurious 6 , 7 ) . The dynamic valgus position of the knee during single-leg activities is one movement pattern that has received much attention in the literature and has been associated with higher rates of knee injuries 8 , 9 ) .…”
Section: Introductionmentioning
confidence: 99%